Size and distributional pattern of pension-related tax expenditures in European countries - Salvador Barrios Cobos; Flavia Coda Moscarola; Francesco Figari; Luca Gandullia (University of Essex, Institute for Social and Economic Research (ISER), 2018)
Policy discussions on pension systems generally focus on their sustainability and design, including retirement age, income reference and contributory period, with relatively little attention devoted to the tax treatment of pension contributions and pension benefits. However, tax expenditures - defined as deviations from an agreed benchmark tax system - are widely used in EU Member States, and little is known about their fiscal and distributional impact. This paper quantifies the fiscal and distributional impact of tax expenditures related to public and private contributory pension schemes, affecting both contributions and pension benefits, in 28 European countries using EUROMOD, the EU-wide microsimulation model. We find that pension-related tax expenditures can have a sizeable impact on revenue and strong effects on inequality and poverty. Tax expenditures tend to be progressive on two levels: first, among pensioners, by favoring those with lower incomes, mainly as a result of the preferential treatment given to pension incomes; and, second, among people of working age, through a partial or no deduction of pension contributions, draining resources from those at the top of the income distribution. Moreover, embracing a lifetime perspective, tax expenditures tend to redistribute resources in favor of women and low educated individuals.
Keywords: C53; D31; H24; H31; H55; 330; tax expenditures; pensions; microsimulation; EUROMOD